Model Pengembangan Ekonomi Produktif Melalui Inovasi Bakso Jamur Pada Kelompok Tani “Elok Mekar Sari” Urban farming Surabaya - Endah Budirti; Fausta Ari Barata; Muhammad Yasin (Lembaga Pengembangan Kinerja Dosen, 2026)
The community service program conducted by lecturers from the Faculty of Economics and Business, Universitas 17 Agustus 1945 Surabaya, aimed to enhance the productive economy of the “Elok Mekar Sari” Farmer Group through the innovation of processing mushrooms into mushroom meatballs as a value-added food product. The program was implemented using a participatory approach, including training in production processes, product packaging and branding, digital marketing, and continuous business mentoring. The entire series of activities was designed to improve the capacity of farmer group members to develop businesses based on local potential. The results demonstrated an improvement in participants’ skills in processing mushrooms into products with higher economic value, applying more modern and attractive packaging techniques, and utilizing social media as a promotional and marketing platform. In addition, the program increased entrepreneurial motivation, strengthened collaboration among farmer group members, and supported the development of healthy food MSMEs based on urban farming. The diversification of mushroom products into mushroom meatballs was proven to increase commodity value, expand new business opportunities, and has the potential to serve as an innovative and sustainable model for empowering urban communities that can be replicated by other community groups with similar characteristics.